UPAYA SATLANTAS POLRES KUTAI TIMUR DALAM MENERTIBKAN PELANGGARAN LALU LINTAS DI WILAYAH HUKUM POLRES KUTAI TIMUR - DIMAS DWI NUR ROHIM (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT Transportation is a very important and strategic means in smoothing the economy, and other activities with the aim of strengthening unity and integrity and influencing aspects of national and state life. Increasing population and growing economy of the economy in developing countries such as Indonesia requires people to have high mobility in order to meet their daily needs. Guidance on the attitudes and compliance of motor vehicle drivers regarding traffic regulations has been carried out by the East Kutai Police Traffic Unit, but with an imbalance between the number of motorized vehicle ownership and access not increasing this road, it has resulted in various types of traffic violations. which is difficult to minimize. Driving by car or motorcycle on a big road that has super busy traffic traffic is certainly not an easy and comfortable thing. In addition to being troubled by traffic jams, we are often treated to some